2021
DOI: 10.1097/aud.0000000000001068
|View full text |Cite
|
Sign up to set email alerts
|

Applying Kurtosis as an Indirect Metric of Noise Temporal Structure in the Assessment of Hearing Loss Associated With Occupational Complex Noise Exposure

Abstract: Objective: The association of occupational noise-induced hearing loss (NIHL) with noise energy was well documented, but the relationship between occupational noise and noise temporal structure is rarely reported. The objective of this study was to investigate the principal characteristics of the relationship between occupational NIHL and the temporal structure of noise. Methods: Audiometric and shift-long noise exposure data were collected from 3102 Chinese manufacturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 36 publications
2
33
0
2
Order By: Relevance
“…The more impulsive the noise, the greater the kurtosis. Zhang et al (2021b) reported that kurtosis was significantly associated with the difference of peak SPL (L peak ) minus its L Aeq,8h across different types of work. The temporal structure of a non-Gaussian noise can be indirectly characterized by estimating the kurtosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The more impulsive the noise, the greater the kurtosis. Zhang et al (2021b) reported that kurtosis was significantly associated with the difference of peak SPL (L peak ) minus its L Aeq,8h across different types of work. The temporal structure of a non-Gaussian noise can be indirectly characterized by estimating the kurtosis.…”
Section: Discussionmentioning
confidence: 99%
“…They plotted the dose–response curve between CNE (CNE′) and NIHL prevalence and found that the curve of non-Gaussian noise almost overlapped that of Gaussian noise when using CNE′. Zhang et al (2021b) also plotted the dose–response curves and further calculated the differences in NIHL prevalence between the non-Gaussian noise group and Gaussian noise group; the authors found that after kurtosis adjustment, the average difference of NIHL prevalence significantly decreased from 7.63% to 1.12%. These findings suggested that CNE′ was able to consistently estimate the prevalence of hearing loss across varied noise environments using a single metric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, many industrial noise environments are non-Gaussian noise (Zhou et al, 2020 ). Studies have revealed that complex noise exposure could cause a greater risk of NIHL than Gaussian noise (Zhao et al, 2010 ; Goley et al, 2011 ; Suter, 2017 ; Zhang et al, 2021b ). The energy metric of noise alone does not apply to the assessment of hearing loss caused by non-Gaussian noise in the workplace and the temporal metric of noise should be considered to be a supplemental indicator of NIHL assessment (Davis et al, 2009 , 2012 ; Seixas et al, 2012 ; Xie et al, 2016 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the prevalence of NIHL increased with exposure duration, noise energy levels, sex, and age (Lie et al, 2014 ; Chen et al, 2019 ; Zhou et al, 2020 ; Zhang et al, 2021b ). A total of 24.4% of adults had an audiometric notch in the United States, this was more common among males than females (Carroll et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%